The outcome of transanal endoscopic microsurgery in obese patients. Issue 1 (January 2018) - Fenig, Yaniv; Khoury, Mansour; Schmilovitz-Weiss, Hemda; Gingold-Belfer, Rachel; Nissim Bachar, Gil; Issa, Nidal
Abstract : Background: The prevalence of obesity is as high as one-third of the adult population in the ultrasound. Obese patients operated for rectal cancer are less likely to undergo sphincter-preserving surgery, and have an increased morbidity and mortality. We aim to report the outcomes of transanal-endoscopic-microsurgery (TEM) in obese patients with benign and malignant neoplasms. Materials and methods: An analysis was carried out of all patients undergoing TEM at a single institution between 2004 and 2015. Clinical, demographic, and pathologic data were analyzed in respect to BMI; a dichotomous variable was created categorizing the patients in this retrospective case series as either obese (BMI≥30) or nonobese (BMI<30). Results: Of the 158 patients who underwent TEM during the study period, 51 (32%) were obese and 107 (68%) were nonobese. No significant differences were found in terms of patients' demographics and tumor characteristics. There were no significant differences in operative time [105 min (range: 75–170) and 98 (range: 56–170), respectively, P =0.2], hospital length of stay [3 days (range: 2–6) and 4 (range: 2–12), respectively, P =0.48], or complication rates (20 and 23%, respectively, P =0.68). Conclusion: TEM is a safe procedure for rectal neoplasms in the obese population. We found no difference in surgical time and completeness of specimen resection, and no increase in complications or length of stay in the hospital in obese versus nonobese patients. As for selected high risk patients, the TEM may be of benefit in obese patients with T1/T2N0M0 rectal cancer.